The effects of heat-moisture treatment on avocado starch granules: thermoanalytical and structural analysis - Lacerda, Luiz Gustavo; Carvalho Filho, Marco Aurelio da Silva; Bauab, Tabata; Demiate, Ivo Mottin; Denck Colman, Tiago Andre [UNESP]; Pereira Andrade, Marina Morena; Schnitzler, Egon (Springer, 2015)
The avocado (Persea americana, Miller) is a very popular tree worldwide. It is native to Central/North America (Mexico) and its fruit is healthy and is consumed in large quantities worldwide. Several studies revealed that a diet enriched with avocado fruit lowers total cholesterol and low-density lipoproteins levels without changing high density lipoprotein levels. The seeds of the avocado constitute a high percentage of the fruit's mass and they are often discarded as industrial waste. These seeds contain an important amount of starch and there is lack of study regarding the physicochemical properties of this biopolymer. Heat-moisture treatment (HMT) of starch is a physical method considered to be natural; it consists of heating starch at a temperature above its gelatinisation point, with insufficient moisture (< 35 %) to cause gelatinisation. Stoichiometrically distilled water (up to 10, 20 and 30 %, w/w) was added to untreated samples of avocado starch (moisture around 9 %) and then each sample was homogenised and sealed into 100 mL pressure flasks, sealed tightly with a cap and maintained in an autoclave at 120 A degrees C for 60 min. After this time, each sample was investigated using the following techniques: simultaneous thermogravimetry-differential thermal analysis; differential scanning calorimetry; non-contact atomic force microscopy; rapid viscoamylographic analysis; atomic force microscopy; and X-ray powder pattern diffractometry.
Keywords: Avocado starch; Heat-moisture treatment; Thermal analysis; Gelatinisation